Methods for analysis and monitoring of heavy metals in the environment - A. R. Tsygankova; S. A. Gulyaev; L. S. Adamenko; M. A. Shestopalov (Юг России: экология, развитие, 2024)
This review surveys capabilities of modern instrumental analytical methods that provide low limits of detection for a wide range of elements. Some elements have their own toxic forms, so their identification is of particular importance. Researchers pay increased attention to the content of cadmium and lead due to their high immediate and delayed toxicity.It should be noted that those instrumental methods of analysis that are used to determine these important ecotoxicants are often used to determine other heavy metals. The following objects of analysis are considered – natural, river, sea waters; brines; bottom sediments; plants, including medicinal ones; precipitation; soil; as well as whole blood and blood serum; hair and animal fur; animal organs and tissues. Special attention is paid to eliminating matrix influences and reducing limits of detection using concentration procedures. Various types of extraction, sorption, precipitation, chemical transformation (hydride generation, etc.) are considered and applied to biological and environmental objects.The capabilities of modern instrumental methods of analysis for the determination of heavy metals and important ecotoxicants are considered and compared – single‐element (ETAAS, IVA, etc.) and multi‐element (ICP AES, ICP MS, XRF, etc.). The data is structured in the form of a table, which shows specific analysis methods, indicating the method of sample preparation and/or features of instrumental determination, a list of elements to be determined and the limits of detection.